Study of Fat, Lactose, and Protein Concentrations of Holstein Friesian Cow's Milk Early Lactation - Tri Eko Susilorini; Hanum Muarifa; Ike Mawarni Handayani; Aditya Cahya Wardhana; Puguh Surjowardojo; Rifa'i Rifa'i (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2022)
This study aims to determine the concentration of lactose, fat, and protein in FH cow's milk at the beginning of lactation which is intensively reared at the People's Farm of the Dairy Cattle Farming Cooperative (KPSP) located in Tutur District, Nongkojajar, Pasuruan Regency, East Java Province, Indonesia. The research material used was fresh milk from lactating dairy cows. The research method used is laboratory analysis with purposive sampling technique. FH dairy cows that were in 3rd lactation period was taken as samples on the 1st, 2nd, and 3rd milking days in the morning and evening milking times. Data were analyzed descriptively and qualitatively. The results showed that the average fat concentration of FH cow's milk in the morning milking was 4.23±0.68%, while in the afternoon milking was 4.99±0.65%. The average lactose concentration in the morning milk was 4.10±0.66%, while in the afternoon milk was 4.48±0.71%. The average protein concentration in the morning milking was 3.23±0.94%, while in the afternoon milking was 3.32 ±0.65%. This study concluded that the high concentration of fat, lactose, and protein in the afternoon milking was caused by the shorter time interval between morning and evening milking than the afternoon to morning milking time.The concentration of fat, lactose, and protein in FH cow's milk, which is higher than the SNI standard, is due to several factors including environmental, nutritional, climatological, and managerial factors. The factors are inseparable from each other in influencing milk quality.The quality of fresh milk produced by the Dairy Cow Farming Cooperative People's Farm (KPSP) located in Tutur District, Nongkojajar, Pasuruan Regency, East Java Province, Indonesia is in good condition, safe, and suitable for consumption as milk quality standards meet SNI No. 01-3141.1-2011.